The Significant Motivation, Communication, and Work Discipline on Employee Performance: Evidence Alfa and Omega Company in South Jakarta - Sosiatri, Rob; Varindhayani, Varindhayani (Jurnal Mandiri : Ilmu Pengetahuan, Seni, dan Teknologi, 2021)
The purpose of this study was to determine the effect of motivation, communication and work discipline on employee performance at Alfa and Omega Company either partially or simultaneously. The method used is the descriptive method. The sampling technique used is saturated sampling using a sample of 70 respondents. Data analysis used validity test, reliability test, classical assumption test, regression analysis, correlation coefficient analysis, coefficient of determination analysis and hypothesis testing. The results of this study are motivation has a significant effect on employee performance partially. Communication has a significant effect on employee performance partially Work discipline has a significant effect on employee performance partially. Motivation, communication and work discipline simultaneously have a significant effect on employee performance.